Penyuluhan Tentang Kesehatan Gigi Dan Mulut Pada Anak Sekolah Dasar - Machrumnizar Machrumnizar; Suriyani Tan (CV. Multi Kreasi Media, 2022)
Sugary foods and drinks are defined as foods that contain high levels of sugar. The high sugar content in these foods or beverages generally comes from added sweeteners. Sugary foods and drinks affect human health. If sugary foods and drinks are consumed for a long period of time and in excessive proportions, health problems such as obesity, diabetes mellitus and dental and oral health can occur. School-aged children are consumers who consume a lot of sugary foods and drinks. The incidence of dental caries also often occurs in school children due to consumption of sugary foods and drinks. The purpose of this community service activity is to provide counseling to school children about the risks of consuming sugary foods and drinks, as well as provide education about dental and oral health.